Method for the Accelerated Testing of the Durability of a Construction Binder using the Arrhenius Approach - Fridrichová, Marcela; Dvořák, Karel; Gazdič, Dominik (De Gruyter, 2016)
The single most reliable indicator of a material’s durability is its performance in long-term tests, which cannot always be carried out due to a limited time budget. The second option is to perform some kind of accelerated durability tests. The aim of the work described in this article was to develop a method for the accelerated durability testing of binders. It was decided that the Arrhenius equation approach and the theory of chemical reaction kinetics would be applied in this case. The degradation process has been simplified to a single quantifiable parameter, which became compressive strength. A model hydraulic binder based on fluidised bed combustion ash (FBC ash) was chosen as the test subject for the development of the method. The model binder and its hydration products were tested by high-temperature X-ray diffraction analysis. The main hydration product of this binder was ettringite. Due to the thermodynamic instability of this mineral, it was possible to verify the proposed method via long term testing. In order to accelerate the chemical reactions in the binder, four combinations of two temperatures (65 and 85°C) and two different relative humidities (14 and 100%) were used. The upper temperature limit was chosen because of the results of the high-temperature x-ray testing of the ettringite’s decomposition. The calculation formulae for the accelerated durability tests were derived on the basis of data regarding the decrease in compressive strength under the conditions imposed by the four above-mentioned combinations. The mineralogical composition of the binder after degradation was also described. The final degradation product was gypsum under dry conditions and monosulphate under wet conditions. The validity of the method and formula was subsequently verified by means of long-term testing. A very good correspondence between the calculated and real values was achieved. The deviation of these values did not exceed 5 %. The designed and verified method does not also consider the influence of other effects, for instance, chemical corrosion or corrosion caused by frost-thaw cycles. However, this method could be a supplementary tool applicable to the study of degradation processes and the estimation of a binder´s durability as well.

The single most reliable indicator of a material’s durability is its performance in long-term tests, which cannot always be carried out due to a limited time budget. The second option is to perform some kind of accelerated durability tests. The aim of the work described in this article was to develop a method for the accelerated durability testing of binders. It was decided that the Arrhenius equation approach and the theory of chemical reaction kinetics would be applied in this case. The degradation process has been simplified to a single quantifiable parameter, which became compressive strength. A model hydraulic binder based on fluidised bed combustion ash (FBC ash) was chosen as the test subject for the development of the method. The model binder and its hydration products were tested by high-temperature X-ray diffraction analysis. The main hydration product of this binder was ettringite. Due to the thermodynamic instability of this mineral, it was possible to verify the proposed method via long term testing. In order to accelerate the chemical reactions in the binder, four combinations of two temperatures (65 and 85°C) and two different relative humidities (14 and 100%) were used. The upper temperature limit was chosen because of the results of the high-temperature x-ray testing of the ettringite’s decomposition. The calculation formulae for the accelerated durability tests were derived on the basis of data regarding the decrease in compressive strength under the conditions imposed by the four above-mentioned combinations. The mineralogical composition of the binder after degradation was also described. The final degradation product was gypsum under dry conditions and monosulphate under wet conditions. The validity of the method and formula was subsequently verified by means of long-term testing. A very good correspondence between the calculated and real values was achieved. The deviation of these values did not exceed 5 %. The designed and verified method does not also consider the influence of other effects, for instance, chemical corrosion or corrosion caused by frost-thaw cycles. However, this method could be a supplementary tool applicable to the study of degradation processes and the estimation of a binder´s durability as well.
Method for the Accelerated Testing of the Durability of a Construction Binder using the Arrhenius Approach
Keywords: Arrhenius approach; Accelerated testing; Durability; Hydraulic binders; Hydration; Arrhenius approach; Accelerated testing; Durability; Hydraulic binders; Hydration